PROFIL MAHASISWA UNIVERSITAS MUHAMMADIYAH GRESIK TAHUN AKADEMIK 2013-2014 - admin admin; Noor Amirudin; Aslich Maulana (TAMADDUN : Jurnal Pendidikan dan Pemikiran Keagamaan, 2017)
Profile university of muhammadiyah Gresik students 2013-2014 academic year. This study aimed to describe the profile of university students of Muhammadiyah Gresik academic year 2013-2014. With the boundary problem is focused on students of the faculty of Islamic studies Islam UMG. This descriptive study conducted at the University of Muhammadiyah Gresik by using a questionnaire response. The sample was taken from number 511 4 % of it is 28 people. Data were analyzed descriptively qualitative. The results showed that the profile of university students of Muhammadiyah Gresik respectively are: the origin student area of Gresik 97 %, sex men 51 % and women 49 %, background Muhammadiyah overall 30 %, and beground family organization Muhammadiyah 45 % , Nahdlatul Ulama ' 45 %, and 10 % of National and ability of parents belonged to a pretty average.